2019
DOI: 10.2147/jhc.s186239
|View full text |Cite
|
Sign up to set email alerts
|

<p>LI-RADS: a conceptual and historical review from its beginning to its recent integration into AASLD clinical practice guidance</p>

Abstract: The Liver Imaging Reporting and Data System (LI-RADS®) is a comprehensive system for standardizing the terminology, technique, interpretation, reporting, and data collection of liver observations in individuals at high risk for hepatocellular carcinoma (HCC). LI-RADS is supported and endorsed by the American College of Radiology (ACR). Upon its initial release in 2011, LI-RADS applied only to liver observations identified at CT or MRI. It has since been refined and expanded over multiple updates to now also ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 35 publications
0
61
0
2
Order By: Relevance
“…The webinars' content was carefully designed to cover a comprehensive list of topics crucial for practicing radiologists interested in liver imaging. Key themes included Liver Imaging Reporting and Data System (LI-RADS) [9] , liver imaging techniques, the correlation between radiological and pathological findings in the liver, and image-guided therapies for hepatocellular carcinoma. Each webinar included one topic, but some topics were discussed over several webinars.…”
Section: Methodsmentioning
confidence: 99%
“…The webinars' content was carefully designed to cover a comprehensive list of topics crucial for practicing radiologists interested in liver imaging. Key themes included Liver Imaging Reporting and Data System (LI-RADS) [9] , liver imaging techniques, the correlation between radiological and pathological findings in the liver, and image-guided therapies for hepatocellular carcinoma. Each webinar included one topic, but some topics were discussed over several webinars.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the long examination times, limited scanner access, and high exam cost associated with MRI are considered prohibitive for routine screening. Complete‐protocol diagnostic liver MRI (cMRI) as recommended by LI‐RADS can require ~40 minutes of "room time" (including patient preparation, image acquisition, room turnover) during which a series of noncontrast sequences (T 2 ‐weighted, T 1 ‐weighted in‐ and opposed‐phase, diffusion‐weighted) are performed followed by DCE sequences before and after intravenous gadolinium‐based contrast agent (GBCA) injection . Previous models have shown that a complete‐protocol diagnostic MRI is not cost‐effective for screening of the cirrhosis population .…”
mentioning
confidence: 99%
“…Due to the heterogeneity of HCC features over hepatocarcinogenesis, the complexity of treatment of these patients, and the possibility of other malignant lesions in cirrhotic patients, a more reproducible and objective system of classification of focal hepatic lesions has become necessary in this group of high-risk patients for HCC. In this context, the LI-RADS ® (Liver Imaging Reporting And Data System) emerged with the aim of standardizing the imaging technique and terminology used to describe focal liver lesions, as well as to assist in the interpretation of results and in the standardization of reports (79)(80)(81) .…”
Section: Radiological Diagnosismentioning
confidence: 99%